Quantitative Measurement of Naïve T Cell Association With Dendritic Cells, FRCs, and Blood Vessels in Lymph Nodes - Tasnim, Humayra; Fricke, G. Matthew; Byrum, Janie R.; Sotiris, Justyna O.; Cannon, Judy L.; Moses, Melanie E. (Frontiers in Immunology, 2018)
T cells play a vital role in eliminating pathogenic infections. To activate, na¨ıve T cells search 5 lymph nodes (LNs) for dendritic cells (DCs). Positioning and movement of T cells in LNs is 6 influenced by chemokines including CCL21 as well as multiple cell types and structures in the 7 LNs. Some previous studies have suggested that T cell positioning facilitates DC colocalization 8 leading to T:DC interaction. Despite the influence chemical signals, cells, and structures can have 9 on na¨ıve T cell positioning, relatively few studies have used quantitative measures to directly 10 compare T cell interactions with key cell types. Here we use Pearson correlation and normalized 11 mutual information (NMI) to quantify the extent to which na¨ıve T cells spatially associate with DCs, 12 fibroblastic reticular cells (FRCs), and blood vessels in LNs. We measure spatial associations in 13 physiologically relevant regions. We find that T cells are more spatially associated with FRCs 14 than with their ultimate targets, DCs. We also investigated the role of a key motility chemokine 15 receptor, CCR7, on T cell colocalization with DCs. Surprisingly, we find that CCR7 deficiency 16 does not decrease na¨ıve T cells association with DCs, in fact, CCR7-deficient T cells show slightly 17 higher DC association compared with wild type T cells. By revealing these associations, we gain 18 insights into factors that drive T cell localization, potentially affecting the timing of productive T:DC 19 interactions and T cell activation.